Principals’ Perceptions on Admission Services in Kwara State Secondary Schools, Nigeria: A Phenomenology Approach - YUSUF SULEIMAN; ZAHYAH HANAFI; MUHAJIR THANSLIKAN (Universitas Jambi, Indonesia, 2019)
Admission service is an essential service that is needed for the implementation of school programmes and for students’ academic success in secondary schools. Therefore, this study investigated principals’ perceptions on admission services in secondary schools. The research design adopted for the study is phenomenology approach. The participants of the study consist of all principals in Kwara state secondary schools. Purposive and convenience sampling techniques were used to select 20 principals as participants needed for the study. Instrument titled “Interview Protocol on Admission Services IPAS” was used to elicit views on admission services from the participants. Findings of the study revealed that effective admission service had a link with students’ academic achievement in school. Specifically, it indicated that students who went through initial admission screening, such as entrance examination and oral interview performed excellently when given admission. Also, their views revealed that admission service was one of the fundamental services in school system and its importance cannot be underestimated. Finally, it was suggested that proper planning of admission process should be put in place to ensure good admission service exercise in the school system.